Perspektif Hukum Ekonom Syariah Tentang Praktik Akad Rah Sawah (Studi Kasus Di Kp. Mariuk Ds. Maripari Kec. Sukawening Kab. Garut) - Gausian, Gini; Putri, Alma Amelia (Jurnal Hukum Ekonomi Syariah, 2023)
In a pawn transaction, a person lends something to another person as collateral for future debts. For example, the way the people of Mariuk Village get money is by borrowing from each other. They do so by agreeing to sell something (usually their rice field) to people who will then give them the money they need. After that, both parties draw up a contract to track the loan and ensure that it is always paid back. But when a pawn transaction is made, the terms of the agreement are not always followed. This can cause problems for both the pawnshop and the person taking the pawn. In some cases, this can be seen as a serious violation of Sharia economic law. The purpose of this study is to determine the rice field pawn system that occurs in Mariuk Village, Maripari Village, to determine the factors that encourage people to choose rice pawns in Mariuk Village, Maripari Village, and to find out the review of Sharia Economic law on contracts in the practice of rice field rahn (pawn) in Mariuk Village, Maripari Village, Sukawening District, Garut Regency. This research is included in the type of qualitative research with data collection techniques used, namely interviews, observation, and documentation. From this data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it was found that the implementation of rice field pawning in Maripari Village, Sukawening District, Garut Regency had been carried out long ago for reasons of economic problems and was legal in accordance with the provisions of Sharia Economic Law even though the pawn process was only carried out orally, namely the rahin came and offered his rice field to murtahin to be mortgaged with the intention of obtaining a loan of some money from the meeting, rahin and murtahin held Deal.  Keywords: Sharia Economic Law, Akad Rahn,